2002
DOI: 10.3171/jns.2002.96.1.0043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic incidental aneurysms: review of 4568 arteriograms

Abstract: While keeping in mind appropriate caveats in extrapolating from these data, the prevalence rate of asymptomatic unruptured aneurysms found in the present study allows an estimation of the yearly rate of rupture of these lesions. The authors suggest that this yearly rate of rupture falls within the range of 1 to 2%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
1
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(106 citation statements)
references
References 57 publications
5
92
1
8
Order By: Relevance
“…[8][9][10] The influence of parent vessel geometry was reported by Hassan et al 11 Castro et al 12 highlighted the importance of proper modeling for the proximal portions of the parent vessel, a procedure that can strongly influence the results on the basis of the aneurysm orifice and parent artery shape. Hoi et al 13 demonstrated the effect of arterial geometry on the growth of the aneurysm: More tortuous arteries and wide-neck aneurysms were subjected to higher hemodynamic stresses, particularly on the distal parts of the neck.…”
mentioning
confidence: 99%
“…[8][9][10] The influence of parent vessel geometry was reported by Hassan et al 11 Castro et al 12 highlighted the importance of proper modeling for the proximal portions of the parent vessel, a procedure that can strongly influence the results on the basis of the aneurysm orifice and parent artery shape. Hoi et al 13 demonstrated the effect of arterial geometry on the growth of the aneurysm: More tortuous arteries and wide-neck aneurysms were subjected to higher hemodynamic stresses, particularly on the distal parts of the neck.…”
mentioning
confidence: 99%
“…21,34, 70 Winn et al 150 found that 80% of aneurysmal SAH resulted from aneurysms that were smaller than 10 mm in their greatest diameter. They also suggested that the yearly rate of rupture of intracranial aneurysms falls between 1% and 2%.…”
mentioning
confidence: 99%
“…The estimated prevalence of clinically relevant intracranial aneurysms ranges between 0.5 and 1% [1][2][3][4] . The incidence of serious cerebrovascular conditions has substantially decreased in the last 3 decades 5 .…”
mentioning
confidence: 99%